Psycho-emotional disablism: a differentiated process - Halvor Hanisch (Scandinavian Journal of Disability Research, 2013)
This article presents analyses of data from a Norwegian survey. By way of descriptive statistics and linear regression analyses, the study investigates the relations between disability, psycho-emotional well-being, social participation, bullying and violence. It is demonstrated that disability is strongly associated with low psycho-emotional well-being. Relying on Carol Thomas' concept of ‘barriers to being’, it is argued that this finding testifies to a disabling process. Her work also suggests that this process is compounded with other disabling processes such as barriers to social participation. However, the empirical findings presented in this article do not suggest such convergence. Instead, bullying and violence prove to be more important than one might imagine. It is argued that disabling processes should be conceptualized as differentiated rather than compounded, and that research on violence could provide soil for theoretical development.